Huaier shows anti‐cancer activities by inhibition of cell growth, migration and energy metabolism in lung cancer through PI3K/AKT/HIF‐1α pathway. Issue 4 (30th December 2020) - Liu, Xiangli; Liu, Lidan; Chen, Keyan; Sun, Lei; Li, Wenya; Zhang, Shuguang
Abstract: Huaier has been verified to have anti‐cancer effects on many tumours. However, little information is available about the effects of Huaier on non‐small cell lung cancer (NSCLC). We sought to probe the anti‐cancer effects and related mechanisms of Huaier on lung cancer. A549 cells were pre‐treated with 2, 4 and 8 mg/mL Huaier at different time points. Thereafter, cell viability was analysed by CCK‐8 and the migration and invasion were detected by Scratch test and Transwell chamber migration assay. Moreover, ELISA, Western blot, shRNA transfection and RT‐PCR were conducted to discover the related gene and protein expressions of energy metabolism and phosphatidylinositol 3‐kinase (PI3K)/AKT/hypoxia‐inducible factor 1α (HIF‐1α) pathway. Furthermore, tumour xenografts were accomplished to inspect the anti‐cancer effects of Huaier. Our consequences suggested that Huaier considerably repressed cell viability and migration in a dose‐dependent way. In addition, Huaier statistically suppressed glycolysis, glucose transport and lactic acid (LA) accumulation. Besides, we detected that Huaier could inactivate the PI3K/AKT/HIF‐1α pathway. The in vivo data confirmed that Huaier obviously decreased tumour volume and tumour growth, reduced the glycolysis, glucose transport and HIF‐1α expression in the tumour‐bearing tissues. Our results suggested Huaier revealed anti‐tumour effects in both in vivo and in vitro possibly through PI3K/AKT/HIF‐1α pathway.